Effect of Low Nutrition and T-2 Toxin on C28/I2 Chondrocytes Cell Line and Chondroitin Sulfate–Modifying Sulfotransferases. (December 2021) - Deng, Huan; Chilufya, Mumba Mulutula; Liu, Jiaxin; Qiao, Lichun; Xiao, Xiang; Zhao, Yan; Guo, Ziwei; Lv, Yizhen; Wang, Wenyue; Zhang, Jiaheng; Han, Jing
Objective: To investigate the effects of low nutrition and trichothecenes-2 toxin (T-2) on human chondrocytes cell line C28/I2 and the gene expression levels of some chondroitin sulfate (CS)–modifying sulfotransferases. Methods: The chondrocytes were divided into 4 intervention groups: (a) control group (Dulbecco's modified Eagle's medium/Nutrient Mixture F-12 [DMEM/F-12] with fetal bovine serum [FBS]), (b) low-nutrition group (DMEM/F-12 without FBS), (c) T-2 group (DMEM/F-12 with FBS plus 20 ng/mL T-2), and (d) combined group (DMEM/F-12 without FBS plus 20 ng/mL T-2). Twenty-four hours postintervention, ultrastructural changes in the chondrocytes were observed by transmission electron microscopy (TEM). Live cell staining and methyl thiazolyl tetrazolium (MTT) assay were performed to observe cell viability. The expression of CS-modifying sulfotransferases, including carbohydrate sulfotransferase 3, 12, 13, 15 (CHST-3, CHST-12, CHST-13, and CHST-15, respectively), and uronyl 2-O-sulfotransferase (UST) were examined by quantitative real-time polymerase chain reaction (RT-qPCR) analysis. Results: The cells in the T-2 group and combined group had significantly lower live cell counts and relative survival rates than the control group. TEM pictures revealed decreased electron density of mitochondria in the low-nutrition group. The T-2 group and combined group both caused mitochondrial swelling, damage, and reduction in mitochondrial number. RT-qPCR showed a trend of altered expression of CHST and increased expression of UST genes under low-nutrition, T-2 toxin and combined interventions. Conclusions: These results show early-stage Kashin-Beck disease chondrocyte pathophysiology, consisting of chondrocyte cell damage and compensatory upregulation of CHST and UST genes.